(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The increasing accumulation of organic waste poses significant environmental challenges and necessitates innovative strategies for sustainable waste management. This study explores the potential of biochemical catalysis as a method for converting organic waste into high-value chemical products. Biochemical catalysis utilizes enzymes and microorganisms to accelerate chemical reactions under mild conditions, offering an environmentally friendly and energy-efficient approach to waste valorization. By employing advanced catalytic processes, various types of organic waste, including agricultural residues, food waste, and industrial by-products, can be transformed into valuable chemicals such as biofuels, biopolymers, and specialty chemicals. This paper reviews the current state of research in this field, discusses the mechanisms and pathways of biochemical catalysis, and evaluates the potential economic and environmental benefits. The findings highlight the promise of biochemical catalysis in contributing to a circular economy by turning waste into resources and reducing the reliance on fossil fuels, thus paving the way for more sustainable industrial practices.